The COMMUNITARIAN AND INTERGOVERNMENTAL DIMENSION OF THE EU VISA LAW - Cesarz, Maciej Zbigniew (Review of European and Comparative Law, 2019)
This article explores the development of EU visa policy with special emphasis put on legal and institutional dimension. Basing on a formal analysis of primary and secondary law of the European Union and literature of the subject, it claims that intergovernmental roots of common visa policy strongly affect the current structure of EU regulations on visas. The research is focused on the formal development in this area of integration with particular attention paid to intergovernmental dimension which is still present in the framework of Schengen visa regime. Visa facilitation agreements as part of EU visa law as well as political determinants of common visa policy are also examined. The article concludes that visa issuing still remains a complex matter, characterized by dispersion of visa acquis due to separate provisions that still remain in force and which presents a mix of hard and soft law. Since the Member States have retained the right to issue national, long-term visas and the national practice of issuing uniform visas remains varied, the European integration in the area of visas is still incomplete.